The longitudinal associations between filial piety belief and mobile phone addiction: from the perspective of self-determination theory - Wei, Hua; Tang, Jiajia; Xu, Hemuqing; Shi, Juan; Wu, Qiufang; Song, Yuancai (Frontiers in Psychology, 2025)
Based on the dual filial piety model, this study aims to examine the impact of filial piety beliefs on mobile phone addiction. Drawing on self-determination theory, it explores the mediating effect of basic need satisfaction and tests the moderating effect of ego-depletion. Through a 6-month longitudinal study, a total of 1,468 adolescents completed the questionnaires, which included the dual filial piety scale, basic need satisfaction scale, ego-depletion scale, and mobile phone addiction scale. The results showed that reciprocal filial piety belief has a negative impact on mobile phone addiction, while authoritarian filial piety belief has no significant effect on mobile phone addiction. In addition, reciprocal filial piety belief influences mobile phone addiction through the mediating effect of basic needs satisfaction. Reciprocal filial piety belief enhances basic needs satisfaction, which in turn decreases the likelihood of developing mobile phone addiction. Moreover, the effect of basic need satisfaction on mobile phone addiction is moderated by ego-depletion. Specifically, for adolescents with low levels of ego-depletion, basic need satisfaction can reduce mobile phone addiction. In contrast, for adolescents with high levels of ego-depletion, basic need satisfaction has no significant effect on mobile phone addiction.